2021
DOI: 10.1002/ardp.202100092
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 5H‐indeno[1,2‐b]pyridine derivatives: Antiproliferative and antimetastatic activities against two human prostate cancer cell lines

Abstract: This study describes the direct synthesis of 2‐amino‐4‐(phenylsubstituted)‐5H‐indeno[1,2‐b]pyridine‐3‐carbonitrile derivatives 5–21, through sequential multicomponent reaction of aromatic aldehydes, malononitrile, and 1‐indanone in the presence of ammonium acetate and acetic acid (catalytic). The biological study showed that compound 10 significantly impeded proliferation of the cell lines PC‐3, LNCaP, and MatLyLu. The antimetastatic effects of compound 10 could be related with inhibition of MMP9 in the PC‐3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…This literature reveals that 1,2-dihydro naphthalene and 1H-indene coupled heterocyclic compounds possess remarkable anticancer activity. On this basis, and as a continuation of previous work [15,19] we are reporting the synthesis, via a one-pot synthesis from elementary starting materials as methoxy substituted-1-tetralone, aromatic aldehydes substituted, malononitrile, ammonium acetate, acetic acid in toluene of 2-Amino-5,6-dihydro-4-(3 or 4-hydroxy-4 or 3-methoxyphenyl)methoxybenzo[h]-quinoline-3-carbonitrile derivatives and their in vitro evaluation against bloodstream trypomastigotes of T. cruzi (NINOA and INC-5 strains). A study in silico on absorption, distribution, metabolism, excretion, and toxicity (ADME/Tox) profiling to help to describe the molecular properties related to the pharmacokinetic aspects in the human body of these compounds is reported.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…This literature reveals that 1,2-dihydro naphthalene and 1H-indene coupled heterocyclic compounds possess remarkable anticancer activity. On this basis, and as a continuation of previous work [15,19] we are reporting the synthesis, via a one-pot synthesis from elementary starting materials as methoxy substituted-1-tetralone, aromatic aldehydes substituted, malononitrile, ammonium acetate, acetic acid in toluene of 2-Amino-5,6-dihydro-4-(3 or 4-hydroxy-4 or 3-methoxyphenyl)methoxybenzo[h]-quinoline-3-carbonitrile derivatives and their in vitro evaluation against bloodstream trypomastigotes of T. cruzi (NINOA and INC-5 strains). A study in silico on absorption, distribution, metabolism, excretion, and toxicity (ADME/Tox) profiling to help to describe the molecular properties related to the pharmacokinetic aspects in the human body of these compounds is reported.…”
Section: Introductionsupporting
confidence: 65%
“…According to recent reports, it has been found that 2-amino-5,6-dihydro-4-phenylbenzo [h]quinoline-3-carbonitrile derivatives [15], 2-amino-4-benzylpyridine-3-carbonitrile derivatives [16], 2-amino-4-quinolinyl-naphthopyrane-3-carbonitrile derivatives [17], 6,7-Dimethyl-4-(3,4,5-trimethoxyphenyl)-3,4-dihydroquinolin-2(1H)-one (DTDQ) [18], and 2-Amino-4-(phenyl substituted)-5H-indeno[1,2-b]pyridine-3-carbonitrile derivatives [19] are particularly active as anticancer and MMPs inhibitors. This literature reveals that 1,2-dihydro naphthalene and 1H-indene coupled heterocyclic compounds possess remarkable anticancer activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The common heterocycle pyridine possesses various activities like anticancer, antimicrobial, antimalarial, antitubercular, anti-inflammatory, antiproliferative, antiviral, and analgesic activities. [7][8][9][10][11][12][13][14] The other heterocycles like pyrimidine, furan, pyrrole, indole, oxadiazole, benzoxazole, azetidine, thiophene, coumarin, benzofuran, pyrazole, quinoline oxazole, quinazoline, pyrimidine, thiazole, quinoline, pyrazole, and isoxazole also possess various pharmacological activities. [8,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The Food and Drug Administration (FDA)-approved drugs in recent years contain biologically active heterocycles in their structures.…”
mentioning
confidence: 99%